Cloning, overexpression, purification, and physicochemical characterization of a cold shock protein homolog from the hyperthermophilic bacterium Thermotoga maritima. - Welker, C. (Cold Spring Harbor Laboratory Press, 1999)
Thermotoga maritima (Tm) expresses a 7 kDa monomeric protein whose 18 N-terminal amino acids show 81% identity to N-terminal sequences of cold shock proteins (Csps) from Bacillus caldolyticus and Bacillus stearothermophilus. There were only trace amounts of the protein in Thermotoga cells grown at 80 degrees C. Therefore, to perform physicochemical experiments, the gene was cloned in Escherichia coli. A DNA probe was produced by PCR from genomic Tm DNA with degenerated primers developed from the known N-terminus of TmCsp and the known C-terminus of CspB from Bacillus subtilis. Southern blot analysis of genomic Tm DNA allowed to produce a partial gene library, which was used as a template for PCRs with gene- and vector-specific primers to identify the complete DNA sequence. As reported for other csp genes, the 5' untranslated region of the mRNA was anomalously long; it contained the putative Shine-Dalgarno sequence. The coding part of the gene contained 198 bp, i.e., 66 amino acids. The sequence showed 61% identity to CspB from B. caldolyticus and high similarity to all other known Csps. Computer-based homology modeling allowed the conclusion that TmCsp represents a beta-barrel similar to CspB from B. subtilis and CspA from E. coli. As indicated by spectroscopic analysis, analytical gel permeation chromatography, and mass spectrometry, overexpression of the recombinant protein yielded authentic TmCsp with a molecular weight of 7,474 Da. This was in agreement with the results of analytical ultracentrifugation confirming the monomeric state of the protein. The temperature-induced equilibrium transition at 87 degrees C exceeds the maximum growth temperature of Tm and represents the maximal Tm-value reported for Csps so far.